Igneous Rock Associations 5. Oceanic Island Volcanism II: Mantle Processes - Greenough, John; Dostal, Jaroslav; Mallory-Greenough, Leanne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY Oceanic island basalts (OIBs) have been central to understanding evolution of the Earth and mantle because their isolated positions in ocean basins limit the potential for magma contamination by continental crust. Melting processes (e.g., percentage melting) affect OIB chemistry but isotopic and trace-element ratios provide information on mantle-source compositions. They indicate that OIB mantle sources represent mixtures between mid-ocean ridge basalt (MORB) mantle and four other mantle components: EM1 (enriched mantle 1), EM2, HIMU (High U/Pb = Hi µ) and FOZO (FOcal ZOne). Mass-balance and noble-gas arguments indicate that most of the mantle is depleted but He and Ne isotopes, and convergence of Sr-Nd-Pb isotopic arrays suggest that FOZO is a somewhat primitive (unmelted) component common to all oceanic basalt sources. The other components contain "materials" such as basaltic ocean floor (HIMU), pelagic sediments (EM1), oceanic plateaus (EM1), subcontinental lithosphere (EM1, EM2), terrigenous sediments or subducted continental crust (EM2), which have been recycled by subduction processes, and mixed back into the depleted mantle. How these components cycle through the mantle is debated but heterogeneities occur on all length-scales. One school argues that oceanic islands develop above mantle plume convection cells that deliver recycled components and FOZO (lower mantle?) for mixing with depleted upper mantle. Others contend that propagating cracks in the lithosphere create oceanic islands, that plumes do not exist, that the upper and lower mantle are isolated and depleted, and that MORB and OIB form from the same upper-mantle reservoir. Small-scale melting allows OIB to sample local, low-melting-point heterogeneities that are averaged-out by the large-scale melting that forms MORB. These radically different views of mantle structure and composition indicate that OIB will continue to be a focal point in studies of Earth's evolution.